Blood lactate levels are associated with an increased risk of metabolic dysfunction-associated fatty liver disease in type 2 diabetes: a real-world study - Ma, Yi-Lin; Ke, Jiang-Feng; Wang, Jun-Wei; Wang, Yu-Jie; Xu, Man-Rong; Li, Lian-Xi (Frontiers in Endocrinology, 2023)
Aim: To investigate the association between blood lactate levels and metabolic dysfunction-associated fatty liver disease (MAFLD) in type 2 diabetes mellitus (T2DM). Methods: 4628 Chinese T2DM patients were divided into quartiles according to blood lactate levels in this real-world study. Abdominal ultrasonography was used to diagnosis MAFLD. The associations of blood lactate levels and quartiles with MAFLD were analyzed by logistic regression. Results: There were a significantly increased trend in both MAFLD prevalence (28.9%, 36.5%, 43.5%, and 54.7%) and HOMA2-IR value (1.31(0.80-2.03), 1.44(0.87-2.20), 1.59(0.99-2.36), 1.82(1.15-2.59)) across the blood lactate quartiles in T2DM patients after adjustment for age, sex, diabetic duration, and metformin use (all p<0.001 for trend). After correcting for other confounding factors, not only increased blood lactate levels were obviously associated with MAFLD presence in the patients with (OR=1.378, 95%CI: 1.210-1.569, p<0.001) and without taking metformin (OR=1.181, 95%CI: 1.010-1.381, p=0.037), but also blood lactate quartiles were independently correlated to the increased risk of MAFLD in T2DM patients (p<0.001 for trend). Compared with the subjects in the lowest blood lactate quartiles, the risk of MAFLD increased to 1.436-, 1.473-, and 2.055-fold, respectively, in those from the second to the highest lactate quartiles. Conclusions: The blood lactate levels in T2DM subjects were independently associated with an increased risk of MAFLD, which was not affected by metformin-taking and might closely related to insulin resistance. Blood lactate levels might be used as a practical indicator for assessing the risk of MAFLD in T2DM patients.